FACTORS ASSOCIATED WITH SCHOOL ATTENDANCE AMONG PUPIL REFUGEES IN RWAMWANJA REFUGEE SETTLEMENT IN KAMWENGE DISTRICT; A CROSS-SECTIONAL STUDY. - Tuhaisomwe, Nafutari; Muhumuza, Benon; Ecodu, Simon Peter; Okidi, Charles (Student’s Journal of Health Research Africa, 2024)
Introduction The study aimed to investigate the correlation between psychological factors and school attendance among primary school-going refugee pupils in the Rwamwanja refugee settlement, Kamwenge District. Methodology A cross-sectional study involving 205 respondents assessed the impact of psychological factors like depression, anxiety, and stress on school attendance using the Depression, Anxiety, and Stress method. Results The response rate for the survey was 95.1%, with 195 out of 205 surveys completed, surpassing the recommended 70% threshold for data collection (Amin, 2006). A majority of the survey respondents were female (56%), and most of them (67%) fell within the 13-15 age group. Participants hailed from four different countries, with the Democratic Republic of Congo being the most represented (45%), followed by Rwanda (41%), Burundi (8%), and South Sudan (7%). The analysis of psychological factors indicated average scores of 6.7 for depression, 5.9 for anxiety, and 6.2 for stress, with slight variations between those who attended low and high school. The data analysis indicated a strong connection between depression and school attendance, as higher depression scores were correlated with increased attendance (cOR = 1.57, 95% CI = 1.31–1.88, p<0.001). Conversely, anxiety and stress did not exhibit a notable correlation with attendance. Through multivariate regression analysis, accounting for sociodemographic variables such as age, sex, and country of origin, it was confirmed that depression remained significantly linked to school attendance (aOR = 1.59, 95% CI = 1.33–1.91, p<0.001), while anxiety and stress still demonstrated no significant impact. Conclusion The study concluded that psychological factors are crucial in influencing school attendance among refugee pupils, while socio-demographic factors were insignificant. Recommendations The study suggests that interventions focusing on psychological support and addressing socio-economic barriers can improve school attendance among refugee pupils, emphasizing the need for a holistic approach to address their educational needs.